The efficacy and safety of rabbit anti-thymocyte globulin vs rabbit anti-T-lymphocyte globulin in peripheral blood stem cell transplantation from unrelated donors. Issue 2 (1st February 2016) - Huang, Wenrong; Yu, Li; Cao, Tingting; Li, Yanfen; Liu, Zhanxiang; Li, Honghua; Bo, Jian; Zhao, Yu; Jing, Yu; Wang, Shuhong; Zhu, Haiyan; Dou, Liping; et al.
Abstract : The comparative efficacy and safety of antithymocyte globulin (ATG) at fixed doses in patients undergoing allogeneic peripheral blood stem cell transplantation from unrelated donors (UR-PBSCT) has not been evaluated. In this study, the records of 56 patients and 54 patients who received pre-transplant ATG-Thymoglobulin (ATG-T) at a total dose of 10 mg/kg and ATG- Fresenius (ATG-F) at a total dose of 20 mg/kg, respectively, were retrospectively analyzed. ATG-F patients had a significantly lower probability of developing chronic graft-vs-host disease (cGVHD) than those treated with ATG-T ( p = 0.04). ATG-F was associated with a non-significant trend towards lower relapse rates and higher survival at 3- and 5-years of follow-up compared with ATG-T. A significantly greater proportion of ATG-T patients experienced chills and high fever than ATG-F patients ( p < 0.01). The current findings suggest that ATG-F may more effectively and safely prevent cGVHD without increasing relapse rates in patients undergoing UR-PBSCT.